SHARIA FINANCING SOLUTIONS: IMPROVING FINANCIAL LITERACY AND AVOIDING ILLEGAL FINANCING - Halim, Sofyan; Roza, Fachrul; Widyanto, Muhammad Laras (LPPM Univ. Ibn Khaldun Bogor, 2025)
Small and medium enterprises (SMEs) operating in urban villages face significant obstacles stemming from their entanglement in burdensome online usurious loans. These challenges are primarily caused by inadequate financial literacy, limited access to Sharia-compliant financing options, and poor business management practices. As a response, this service initiative has been carefully designed to provide holistic solutions through the provision of Sharia financial literacy education, facilitation of access to Islamic financing, and mentoring in sound business management practices. The main objective of this initiative is to enhance the financial literacy of micro, small, and medium enterprises, liberate them from dependency on interest-based financial products, and strengthen their business management to ensure better structure and sustainability. Furthermore, the program aspires to build connections between entrepreneurs, communities, and Islamic financial institutions, thereby fostering a financial literacy culture that adheres to halal principles and is consistent with Sharia regulations. The anticipated outcomes include improved Islamic financial literacy, the ability to access internal Sharia-compliant financing, the formation of a Sharia-compliant entrepreneurial community, and the implementation of a simplified financial accounting framework. These developments are expected to offer viable solutions that enable entrepreneurs to progress economically without violating Sharia principles, thus promoting a more inclusive and sustainable business ecosystem.